Revitalisasi Usaha Pengrajin Mendong di Sendangsari Minggir Sleman pada Era Pandemi Covid-19: Revitalizing the Business of Mendong Crawings in Sendangsari Minggir Sleman in the Covid-19 Pandemic Era - Suranto Suranto; ‪Dyah Ekaari Sekar Jatiningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Covid-19 pandemic has had a real impact on Micro, Small, and Medium Enterprises in Indonesia, including in the Special Region of Yogyakarta. The Mendong craftsmanship “DERIJI HANDYCRAFT” in Sendangsari Village, Minggir, was among those that were severely affected. This community service activity aims to (1) innovate and catalog products to attract more consumers, (2) train and develop an online product marketing platform for partners, and (3) provide financial management training. Achieving these goals is done through training with discussion methods, lectures, and workshops with partners. The results of this service activity indicate that the program is going well and smoothly. This program can produce products in the form of catalogs and photos of product innovations, social media platforms for online marketing, and software and financial management guides for Micro Enterprises. While the suggestions are submitted from the results of this PPM program, DERIJI CRAFT partners should be able to update their online marketing platforms and socialize them to future generations to maintain sustainability.